Characterological Correlates of Selfie Taking Behavior - Morrison, Todd G; Morrison, Melanie A; Kiss, Mark J.; Gilliland, Eric (Scientific Research Publishing, 2018)
Few researchers have examined selfie taking behavior. To address this gap, 235 participants (age 18 - 60) completed an online questionnaire assessing a variety of psychological factors, personality traits, and selfie taking activities (i.e., frequency of selfies posted to social networking sites [SNSs], time spent editing selfies, and number of selfie takes prior to posting). A number of statistically significant correlations emerged. For example, participants’ levels of neuroticism, social physique anxiety, body-related shame, and concern about physical appearance correlated positively with the amount of time spent editing selfies. As well, group comparisons between selfie (n = 193) and non-selfie takers (n = 42) suggest that the former exhibit higher levels of certain facets of vanity. The implications of these findings and directions for future research are outlined.
Keywords: Social Media; Vanity; Neuroticism; Body Image; Shame; Guilt